Q: What is 2x2 - 9x 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x2 - 9x + 4 = (2x - 1)(x - 4)

2x2-9x+4 = (2x-1)(x-4) when factored

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

-2x2 + 9x - 12 = 0Then apply the quadratic formula.

Related questions

2x2 - 9x + 4 = (2x - 1)(x - 4)

2x2-9x+4 = (2x-1)(x-4) when factored

2x2 + 10 = 9x 2x2 - 9x + 10 = 0 (x - 2)(2x - 5) = 0

(2x + 1)(x + 4)

2x2 + 10 - 9x = 0 or 2x2 - 9x + 10 = 0 So (x - 2)*(2x - 5) = 0

2x2 - 9x = 18 2x2 - 9x -18 = 0 (2x - 18)(x + 9) x= -9 and 9

-2x2 + 9x - 12 = 0Then apply the quadratic formula.

If: 2x2-9x-5 = 0 Then: (2x+1)(x-5) = 0 Therefore:: x = -1/2 or x = 5

(2x + 1)(x + 4) or (2x - 1)(x - 4) depending on the sign of the term in x and 4 being positive.

2x2 - 9x + 10 = 2x2 - 4x - 5x + 10 = 2x(x - 2) - 5(x - 2) = (x - 2)(2x - 5)

Factors are (2x + 1)(x + 4), making x either -0.5 or -0.25

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x